1990
DOI: 10.1161/01.res.67.2.501
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of reperfusion-associated ventricular fibrillation by left ventricular hypertrophy.

Abstract: Important electrophysiological alterations that may predispose hearts to arrhythmias have been described for hypertrophied myocytes, and hypertrophy coupled with ischemia has been associated with an increased incidence of sudden death; however, an influence of hypertrophy on reperfusion arrhythmias has not been previously described. We hypothesized that reperfusion-associated arrhythmias would be potentiated by left ventricular hypertrophy. After induction of renovascular hypertension, 37 awake, unsedated dogs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…HT not only is the most common cause of LVH, but it also accelerates the development of CAD and increases the oxygen demand, creating a highly life-threatening combination that is reflected by the associated increased incidence of SCD (34). According to experimental studies, there is a decreased tolerance to induced ischemia and reperfusion in myocardial hypertrophy (6,8,29,31,33). Several mechanistic factors have been identified, although their relative importance remains to be clarified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HT not only is the most common cause of LVH, but it also accelerates the development of CAD and increases the oxygen demand, creating a highly life-threatening combination that is reflected by the associated increased incidence of SCD (34). According to experimental studies, there is a decreased tolerance to induced ischemia and reperfusion in myocardial hypertrophy (6,8,29,31,33). Several mechanistic factors have been identified, although their relative importance remains to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Some patients with LVH, in particular those with hypertension, also have an increased propensity for developing CAD. Although experimental studies (see DISCUSSION) have shown reduced tolerance to ischemia and subsequent reperfusion in myocardial hypertrophy, including increased dispersion of repolarization, higher incidence of ventricular arrhythmias, and greater infarct size (6,8,29,31,33), the mechanistic interaction between LVH and ischemia has rarely been studied in humans. Because of these experimental observations, we focused on ventricular repolarization and its response to acute ischemia in a human model of coronary occlusion during percutaneous coronary intervention (PCI).…”
mentioning
confidence: 99%
“…These chronic changes may produce a more arrhythmogenic milieu if epicardial CAD does develop. For example, dogs with hypertensive LVH undergoing left coronary artery occlusion had higher propensity for sustained monomorphic VT (41% vs. 6%; p < 0.05) and reperfusion-associated VF (88% vs. 0%; p < 0.05) compared to those that were normotensive; this disparity occurred despite infarct size being comparable across groups [ 18 , 19 ].…”
Section: Basic Science Datamentioning
confidence: 99%
“…1) Several animal studies 2,3) have demonstrated a powerful association between LV hypertrophy and fatal ventricular arrhythmias induced by ischemia and reperfusion. The increased risk of sudden cardiac death in patients with LV hypertrophy may be due to an increased susceptibility to ventricular arrhythmias.…”
mentioning
confidence: 99%